The radiation therapy oncologist’s view of gastric cancer treatment - Oblak, Irena (Onkologija : Slovenian Journal of Oncology, 2014)
Gastric cancer is associated with a poor prognosis. At diagnosis, approximately 50% of patients have a non-resectable disease. In patients who underwent radical resection, the disease recurs in as many as 75%, of which 40-64% are local and/or regional recurrences (2-4). Despite this fact, we are observing that survival of patients has improved over the years. According to the SLORE data, relative 5-year survival was 14.7% in 1985, 17.8% in 1995, 22.1% in 2000 and 25.6% in 2005 (5). Surgical resection of the tumour and regional lymph nodes is the method of choice for treating gastric cancer with no distant metastases. Until 2000, it was also the only treatment method.